[2.2.2]paracyclophane-trienes: attractive monomers for ROMP - Mäker, Dominic; Maier, Christopher; Brödner, Kerstin; Bunz, Uwe H. F. (ACS Macro Letters, 2014)
Three derivatives of 4,7-substituted [2.2.2]paracyclophane-trienes were synthesized and used in ring-opening metathesis polymerization (ROMP), resulting in well-soluble poly(para-phenylenevinylene)s (PPV). The paracyclophane-trienes were prepared using an iterative buildup of a phenylene-ethynylene backbone, followed by a cis selective Grignard reduction and an intramolecular McMurry reaction. The monomers were applied in ROMP to result in well-soluble PPV derivatives with an unusual substituent pattern. The PPVs were spin-coated into amorphous, highly fluorescent films. To the best of our knowledge, we are the first to synthesize 4,7-substituted [2.2.2]paracyclophane-trienes and use them as ROMP monomers.
Gesehen am 31.08.2020